Strategi Pengarusutamaan Gender Di Lembaga Non Pemerintah: Studi Kasus Di Gereja BNKP - Zega, Destri Pinta Sari; Manalu, Dimpos; Pasaribu, Vera A.R. (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2025)
This study examines gender mainstreaming strategies in the BNKP Church as a non governmental institution that plays a crucial role in the social and religious life of the community. The research aims to analyze the strategies implemented by BNKP to promote gender mainstreaming and identify the challenges that persist in the process. This study employs a qualitative method with a descriptive approach, in which data is collected through in-depth interviews with BNKP Synod office administrators and female pastors. The findings indicate that BNKP has implemented various gender mainstreaming strategies, such as providing access to theological education for women, creating opportunities for them to become pastors, and organizing women's empowerment programs. Despite progress in gender mainstreaming within BNKP, further efforts are required to ensure more substantive equality, as BNKP still faces challenges, including a deeply rooted patriarchal culture, gender stereotypes that limit women's roles in leadership, and the double burden that women continue to bear. Gender Mainstreaming, Gender Equality, Women's Leadership, BNKP.